Hubungan antara Penggunaan Aplikasi Membeli Belah atas Talian terhadap Tingkahlaku Pembelian dalam kalangan Pengguna - Hairuzzamri, Haierul Hisyam; Fazian Hashim, (Research in Management of Technology and Business, 2023)
In line with the latest lifestyle changes where human lifestyle conditions are increasingly busy with work that needs to be done to survive in the real world. The use of online shopping applications is increasingly gaining a place in the hearts of consumers. The use of online shopping applications was chosen as an easy step for consumers to shop to get necessities or wants without the need for long queues at store counters. The objective of this study is to examine the factors that motivate consumers to use shopping applications and what are the decision making behavior derived from the progress of use of online shopping applications. The use of likert scale method will be used in this study, to evaluate the factors of the use of online shopping applications by the residents and the decision making behavior. This study is focused on the user community that have currently been using this service, which is an online shopping application. The sample for this study will be 380 respondents out of the total community. Using quantitative methods, online questionnaires and surveys will be used. The data to be obtained from the distributed questionnaires will be analyzed using the Statistical Process for the Social Sciences (SPSS). Based on the research findings that have been obtained, the study can show that the factors that encourage users to use online purchasing applications influence the behavior of the purchasing decision by users. The results of the study analysis and recommendations to online users and traders are stated in the discussion in the analysis of the study findings.